(untitled) (Palíndromo, 2018)
This article proposes to reflect about the Structuring of the Self, created by Lygia Clark from what Juliano Garcia Pessanha denominates as heterotanatography, a confessional speech in which small and large deaths are printed in the record of the narratives. There seems to be a long legacy transmitted by Lygia Clark in anticipating the works of contemporary artists such as Ana Teixeira, Beth Moysés and Isabela Sielski who thematize memory and the heterotanatographic confessions in the nineties.